The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0101-81751999000400025
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the swimming crab Portunus spinimanus Latreille (Crustacea, Decapoda, Brachyura) from Ubatuba, São Paulo, Brazil

Abstract: ABSTRACT. This study analyses some reproductive aspects of Por/unus spinimanus Latreille, 1819, a crab usually commercialized in Ubatuba region. Monthly otter-trawl collections were taken fortwo years along the northern coast of Sao Paulo State, Brazil. The reproductive period was studied based on the frequency of ovigerous females in the population along the year; the frequency of physiologically mature swimming crabs and the type of spawn. The condition of development of ovigerous females ovary was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 6 publications
4
17
0
6
Order By: Relevance
“…The reproductive pattern at Perequê-açu beach was classified as Seasonal Continuous (according to PINHEIRO & TERCEIRO, 2000), corroborating the pattern found in the congener A. patagoniensis (ALVES & PEZZUTO, 1998a), in which both species occurred in subtropical climate areas. The reproductive pattern registered in this study had been described to other Brachyura from the north shore of the state of São Paulo: Callinectes danae Smith, 1869; Portunus spinimanus Latreille, 1819; Callinectes ornatus Ordway, 1863 and Arenaeus cribrarius (Lamarck, 1818) (COSTA & NEGREIROS-FRANSOZO, 1998;SANTOS & NEGREIROS-FRANSOZO, 1999;MANTELATTO & FRANSOZO, 1999;PINHEIRO & TERCEIRO, 2000, respectively). Generally, Brachyura crustaceans from temperate areas present seasonal reproduction, which occurs in the hottest seasons of the year (WARNER, 1977;ASAKURA & KIKUCHI, 1984), while crabs from tropical and subtropical regions have a continuous reproduction throughout the year, usually in approximate rates (SASTRY, 1983).…”
Section: Discussionsupporting
confidence: 67%
“…The reproductive pattern at Perequê-açu beach was classified as Seasonal Continuous (according to PINHEIRO & TERCEIRO, 2000), corroborating the pattern found in the congener A. patagoniensis (ALVES & PEZZUTO, 1998a), in which both species occurred in subtropical climate areas. The reproductive pattern registered in this study had been described to other Brachyura from the north shore of the state of São Paulo: Callinectes danae Smith, 1869; Portunus spinimanus Latreille, 1819; Callinectes ornatus Ordway, 1863 and Arenaeus cribrarius (Lamarck, 1818) (COSTA & NEGREIROS-FRANSOZO, 1998;SANTOS & NEGREIROS-FRANSOZO, 1999;MANTELATTO & FRANSOZO, 1999;PINHEIRO & TERCEIRO, 2000, respectively). Generally, Brachyura crustaceans from temperate areas present seasonal reproduction, which occurs in the hottest seasons of the year (WARNER, 1977;ASAKURA & KIKUCHI, 1984), while crabs from tropical and subtropical regions have a continuous reproduction throughout the year, usually in approximate rates (SASTRY, 1983).…”
Section: Discussionsupporting
confidence: 67%
“…Less than 500 km to the south, Santos and Negreiros-Fransozo (1999) reported the presence of ovigerous females of A. spinimanus in all months, during two years of collection. Branco et al (2002), in southern Brazil, also reported that ovigerous females were continuously present.…”
Section: Population Traits Of Achelous Spinimanusmentioning
confidence: 97%
“…All individuals obtained were grouped in the following demographic categories: adult males, adult females, ovigerous females, and juveniles (checked by the adherence of the abdomen to the thoracic sternites and the stage of the gonads, which are thin and translucent in juveniles). Four developmental stages were characterized in males and females based on size, shape and color of the gonads: immature -IM (no differentiated gonads), rudimentary -RU (gonads are recognized only by magnifying on males and look filamentous, thin and with pale yellow color on females), developing -ED (on males, the gonads are visible in the anterolateral region of the abdominal cavity and the vas deferent can be divided in two different regions, the front one being thinner; on females beginning of ovary maturation with yellow color and the connection between right and left trumpet are clear), and developed -DE (on males, the gonad reaches its highest development, and the vasa deferentia can be clearly divided in front, median and back; females have bright orange ovary which fills almost the whole thoracic cavity) (adapted by Santos and Negreiros-Fransozo, 1999; illustrative photos available on Mantelatto, 1995).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…The presence of spermatophores before the pubertal molt was described for the portunid Arenaeus cribrarius (Lamarck, 1818) (Pinheiro and Fransozo, 1998), which suggests that physiological maturity could be reached before morphological maturity in this family. The physiological maturation of the male reproductive system was studied macroscopically in some species of Portunidae, with respect to color and the volume occupied by the organ in the cephalothoracic cavity (Costa and Negreiros-Fransozo, 1998;Santos and Negreiros-Fransozo, 1999;Mantelatto and Fransozo, 1999). Other criteria also used to determine physiological maturity are the gonadosomatic (GSI) and hepatosomatic (HSI) indices (Mantelatto, 1995), in addition to histological techniques (Johnson, 1980).…”
Section: Introductionmentioning
confidence: 99%